Rheumatoid arthritis 2 - Taylor, Peter C. (Henry Stewart Talks, 2020)
Overview of the management of rheumatoid arthritis, Treatment guidelines, The role of pharmacological and non-pharmacological treatments (NSAIDs, steroids, DMARDs, biologics and targeted synthetic DMARDs), TNF, IL-6, and additional extracellular components as a key therapeutic target